Haematological Abnormalities in Early Abstinent Alcoholics Are Closely Associated with Alterations in Thrombopoietin and Erythropoietin Serum Profiles - Schmitt, Marc; Gleiter, Christoph H.; Nichol, Janet L.; Pralle, Lars; Hasselblatt, Martin; Poser, Wolfgang; Ehrenreich, Hannelore (Thrombosis and Haemostasis, 1999)
Numerous reports exist on haematological pathology in alcoholism. However, no data are available regarding a potential involvement of haematopoietic growth factors in the recovery from alcohol-induced haematological abnormalities upon abstinence. Therefore, thrombopoietin (TPO) and erythropoietin (EPO) serum levels along with haematological and other routine laboratory parameters were closely followed in 14 thoroughly characterized male alcoholic patients over one to five months of controlled abstention from alcohol. Haematological changes in these early abstinent alcoholics consisted predominantly of (a) the well known rebound surge of platelets, (b) an early reticulocyte peak, and (c) persistently low haematocrit levels over months without signs of recovery. Observations on EPO and TPO during early abstinence can be summarized as follows: (1) Increased TPO levels precede the rebound thrombocytosis by several days, (2) both EPO and TPO concentrations are higher in anaemic than in nonanaemic alcoholics, with (3) nonanaemic subjects exhibiting levels of TPO in the range of healthy controls but levels of EPO below controls and (4) TPO concentrations show a stronger correlation with initial haematocrit values than with thrombocyte counts. To conclude, haematological recovery in early alcohol abstinence appears to be, at least in part, growth factor-driven, involving both TPO and EPO, and may reflect an intense interaction of erythro- and thrombopoiesis.
Keywords: Erythropoietin; thrombopoietin; alcoholism; abstinence; trombocytosis